A new species of Linotetranus (Acari : Prostigmata: Linotetranidae) from Iran - Bagheri, Mohammad; Irani-Nejad, Karim Haddad; Kamali, Karim; Khanjani, Mohammad; Saboori, Alireza; Lotfollahi, Parisa (Zootaxa, 2008)
Mites of the family Linotetranidae (Acari: Prostigmata) are unique among the tetranychoid families in that eyes are absent (Meyer & Ueckermann, 1997). They are usually colourless, slender and less than a third of a millimeter in length, and occur mostly in soil. Linotetranids have been reported from moss, soil and rotting trees, but most collection indicate an association with the crown and roots of grass or sedge in dryland habitats (Beard & Walter, 2004). Up to now eight species of the genus Linotetranus have been described in the world. In this paper we describe and illustrate a new species. The terminology and abbreviations follow Lindquist (1985) and all measurements are given in micrometers.